2015
DOI: 10.1016/j.acalib.2015.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Faculty and Librarians' Partnership: Designing a New Framework to Develop Information Fluent Future Doctors

Abstract: Upon faculty request, information literacy instruction was fully integrated into an English for Academic Purposes course for non-native English speaking students pursuing a medical degree at a U.S. institution in the Gulf State of Qatar. Adopting the flipped classroom modality, librarians designed modules to meet the students' information literacy needs while adapting the content to the course syllabus. Content was uploaded to the learning management system, Canvas. Readings, online tutorials, quizzes and assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 15 publications
(10 reference statements)
0
13
0
Order By: Relevance
“…Faculty support is essential for librarians to teach in‐class and allocate time to IL instruction in the weekly timetable. A percentage of the overall grades may also be earmarked for the IL assignments to maintain students’ commitment (Bendriss, Saliba & Bich, ). Librarians and medical faculty can learn from each other as librarian–faculty collaboration will improve the curriculum development, teaching and assessment competencies of librarians and it will also enhance the IL skills of medical faculty members.…”
Section: Discussionmentioning
confidence: 99%
“…Faculty support is essential for librarians to teach in‐class and allocate time to IL instruction in the weekly timetable. A percentage of the overall grades may also be earmarked for the IL assignments to maintain students’ commitment (Bendriss, Saliba & Bich, ). Librarians and medical faculty can learn from each other as librarian–faculty collaboration will improve the curriculum development, teaching and assessment competencies of librarians and it will also enhance the IL skills of medical faculty members.…”
Section: Discussionmentioning
confidence: 99%
“…In an article documenting the process of integrating IL into the EAP curriculum at WCM-Q, Bendriss et al (2015) described how "weekly classroom time was secured as part of the ESL course as well as a percentage of the overall grade was reserved for the IL assessments to maintain student engagement" (p. 827). The Foundation students acquired the skills in IL that were useful in their EAP writing and transferable to their science courses as well as the Global Health Seminar (Bendriss et al, 2015).…”
Section: English For Academic Purposes Coursementioning
confidence: 99%
“…The gender of students was identified in 13 studies with 1361 women and 736 men participating. Five studies reported information about the age range of participants: 17-19 years (* Bendriss et al, 2015), 18+ years (* Henslee et al, 2015), > 24 years (97% of the sample; * Morgan andHart, 2013), 18-42 years (*Schuetze, 2004), and < 20 (43.3%), 20-24 (32.2%), and > 24 (24.5%) years (* Smedley et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Three of the reviewed articles studied the effectiveness of blended approaches to promote academic integrity (Table 3). Bendriss et al (2015) examined an intervention aimed to enhance students' research skills. In this study, students completed four or eight online information literacy modules that included readings, videos, assignments, and quizzes before attending nine weekly face-to-face sessions with a librarian.…”
Section: Blended Instructionmentioning
confidence: 99%